2002
DOI: 10.1002/jbm.a.10341
|View full text |Cite
|
Sign up to set email alerts
|

Polymer design for corneal epithelial tissue adhesion: Pore density

Abstract: A porous polymer is required to sustain corneal epithelial tissue on the anterior surface of an implantable contact lens (corneal onlay). Porosity creates topography on the polymer surface and, if defined, this can be manipulated to elicit a particular tissue response. Previous work identified pores of 100-nm diameter to be the critical size of a discontinuity in a polymer surface to facilitate the migration, stratification, and sustained adhesion of corneal epithelial tissue. Now we address the issue of pore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
0
21
0
1
Order By: Relevance
“…In addition, cells plated on surfaces with microscale pores were unable to form or had very few hemidesmosomes. This study and a subsequent study on the effect of pore density used sheets of epithelial cells (Evans et al, 1999b;Evans et al, 2003) and found that cell-cell signaling influences cell behavior. Our study, in contrast, was focused on individual cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, cells plated on surfaces with microscale pores were unable to form or had very few hemidesmosomes. This study and a subsequent study on the effect of pore density used sheets of epithelial cells (Evans et al, 1999b;Evans et al, 2003) and found that cell-cell signaling influences cell behavior. Our study, in contrast, was focused on individual cells.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, while there have been a number of studies that have investigated the adhesion of sheets of cells on biologically relevant substrata (Evans et al, 1999b;Evans et al, 2003), we know of no previous studies to quantify the strength of cell-substratum adhesion of single cells…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in mind that contact between like cells may cause inhibition of proliferation and growth, 131 cell proliferation may decrease with small distances between holes. To the opposite extreme, however, epithelial cells have been shown to bridge across holes that are approximately 0.893 to 0.143 mm apart, 132 suggesting that contact inhibition may be slowed if the proximity of the neighboring holes is extremely small. To our knowledge, these relationships have not been studied to date to inhibit ventricular catheter obstruction.…”
Section: Architectural Modificationsmentioning
confidence: 98%
“…Pseudopodia play an important role in sensing the stimulus of surroundings and guiding the locomotion of cells [48] . Evans et al [49] investigated the behavior of pseudopodia, and they reported that the occurrence of "contact guidance" was due to the steric hindrance caused REVIEW POLYMER PHYSICS by the "ridges" horizontally perpendicular to groove pattern filopodia and lamellipodium confronted. Teixeira et al [14] and Dalby et al [50] also reported that filopodia and lamellipodium can "sense" the stimulus of the steric hindrance horizontally perpendicular to groove-like pattern.…”
Section: The Function Of Pseudopodiamentioning
confidence: 98%